Ready access to [5,6,5]-Trioxa-spiro and fused ketals via ag-catalyzed cascade annulation of 4-pentyn-1-ols and aldehydes - Vinodkumar, Ramavath; Nakate, Ashwini K.; Gamidi, Rama Krishna; Kontham, Ravindar (Organic Letters, 2024)
In this study, we unveil the versatility of 4-pentyn-1-ols as carbonyl surrogates for the unprecedented synthesis of diverse oxygen heterocycles, including [5,6,5]-bis-spiroketals (trioxadispiroketals) and [5,6,5]-furano-spiroketals related to bioactive natural products. These reactions commence with the pi-activation-induced intramolecular hydroalkoxylation of 4-pentyn-1-ols, yielding cyclic enol ethers, which undergo subsequent three-component annulation with aldehydes in a [2+2+1+1] fashion, resulting in the formation of [5,6,5]-bis-spiroketals. Notably, the distinctive steric features of alkynyl alcohols, particularly those with a secondary or tertiary alcohol functionality, dictate divergent reaction pathways, leading to the formation of [5,6,5]-furano-spiroketals.